Primary Pancreatic Choriocarcinoma Presenting as Pancreatitis - Ramachandran, Biggs Saravanan; Murugesan, Malarvizhi; Ali, Mohammed; Padmanabhan, Purushotaman (JOP. Journal of the Pancreas, 2012)
<!–[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Context Pancreatic cancers can present with pancreatitis or its complications. Pancreatic choriocarcinoma is an extremely rare disease to involve pancreas. Case report A 27-year-old married woman presented to our facility with abdominal pain and fullness of 20-day duration. She was clinically diagnosed as acute pancreatitis with pseudocyst as a complication. Serum amylase was elevated with CT scan of abdomen showing a cystic lesion involving the pancreas. We approached the cyst with endoscopic ultrasonography and cyst fluid was aspirated and analyzed. Cyst fluid amylase was elevated and cytology revealed germ cell tumor. Serum beta human chorionic gonadotropin was elevated. She had a swelling over the jaw which also revealed choriocarcinoma in histopathological examination. Patient was started with chemotherapy. Conclusion We report this case of pancreatic choriocarcinoma due to its extreme rarity and the diagnostic dilemma it posed.